GZ17-6.02 kills prostate cancer cells in vitro and in vivo - Booth, Laurence; Roberts, Jane L.; West, Cameron; Dent, Paul (Frontiers in Oncology, 2022)
GZ17-6.02 is undergoing clinical evaluation in solid tumors and lymphoma. We defined the biology of GZ17-6.02 in prostate cancer cells and determined whether it interacted with the PARP1 inhibitor olaparib to enhance tumor cell killing. GZ17-6.02 interacted in a greater than additive fashion with olaparib to kill prostate cancer cells, regardless of androgen receptor expression or loss of PTEN function. Mechanistically, GZ17-6.02 initially caused peri-nuclear activation of ataxia-telangiectasia mutated (ATM) that was followed after several hours by activation of nuclear ATM, and which at this time point was associated with increased levels of DNA damage. Directly downstream of ATM, GZ17-6.02 and olaparib cooperated to activate the AMP-dependent protein kinase (AMPK) which then activated the kinase ULK1, resulting in autophagosome formation that was followed by autophagic flux. Knock down of ATM, AMPK or the autophagy-regulatory proteins Beclin1 or ATG5 significantly reduced tumor cell killing. GZ17-6.02 and olaparib cooperated to activate protein kinase R which phosphorylated and inactivated eIF2, i.e., enhanced endoplasmic reticulum (ER) stress signaling. Knock down of eIF2 also significantly reduced autophagosome formation and tumor cell killing. We conclude that GZ17-6.02 and olaparib interact to kill prostate cancer cells in vitro by increasing autophagy and by enhancing ER stress signaling. In vivo, GZ17-6.02 as a single agent profoundly reduced tumor growth and significantly prolonged animal survival. GZ17-6.02 interacted with olaparib to further suppress the growth of LNCaP tumors without ultimately enhancing animal survival. Our data support the consideration of GZ17-6.02 as a possible therapeutic agent in patients with AR+ prostate cancer.